The Integration of Naqli Principles in the Design and Conservation of Heritage Buildings in Negeri Sembilan - Nor Syahila Ab Rashid; Madihah Mat Idris; Azhani Abd Manaf (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 10 Issue 2 Page (37–47)